HUBUNGAN ANTARA SELF CONFIDENCE DENGAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMA - Wulandari, Annisa; Nurcahya, Ali; Kadarisma, Gida (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2018)
This study aims to know in depth about the relationship of self-confidence simultaneously to the ability of solving mathematical problems of high school students. The population in this research is one of the high schools in Cililin. The instrument in this research is a test of mathematical problem solving ability of five items, and self confidence questionnaire of students. Methods in this research use correlational research. The results of this research show that there is a relationship between self confidence on the problem solving ability of high school students is correlation value (r) on Pearson Corellation between self confidence with students mathematical problem solving ability is equal to 0,824. From these results indicate the level of relationships that are strong and indicate the direction of a positive relationship.